Explaining how group model building supports enduring agreement. (November 2019) - Scott, Rodney James
Abstract: System dynamics models are typically used to simulate the behaviour of the problem system under discussion environment, to help understand and solve complex problems. Group model building is a social process for including client groups in the system dynamics modelling process. Recent evidence suggests group model building is useful in supporting durable group decisions by supporting the mental models of participants to become more aligned. There have been several mechanisms proposed to explain these effects. This paper creates a combined model that links the five best-supported mechanisms. The combined model suggests five core conditions of group model building that contributes to its success: completing a structured task, producing a tangible artefact, representing system complexity, the portrayal of causal links, and easy modification or transformation of the artefact by participants. Practitioners are encouraged to use group decision approaches that integrate these conditions.